Aloja and añapa, two traditional beverages obtained from Prosopis alba pods: Nutritional and functional characterization. (June 2020) - Rodríguez, Ivana Fabiola; Cattaneo, Florencia; Zech, Ximena Valdecantos; Svavh, Erika; Pérez, María Jorgelina; Zampini, Iris Catiana; Isla, María Inés
Abstract: Aloja is a beverage obtained using natural fermentation, and añapa an unfermented beverage from Prosopis alba pods. This study aimed to determine phytochemical composition and functional properties of añapa and aloja, as well as, their toxicity and sensorial evaluation. In these two beverages, sugars and polyphenols were found to be the main components, soluble proteins being low. The highest total phenolic and flavonoid and non-flavonoid phenolic content was found in aloja. The main phenolic compounds found in both beverages were C-glycosyl flavonoids, derived from apigenin (vicenin II and vitexin) and phenolic acid (cinnamic acid). Ethanol content in aloja was similar to that of commercial beers (between 5.2 and 6.7%). Añapa does not contain ethanol. Both beverages showed high antioxidant potential (scavenging capacity, SC50 values between 0.9 and 8.5 μg GAE/mL). Neither of them was toxic. Sensorial evaluation suggested that both beverages have a good acceptance. These studies could also lead to the re-introduction of forgotten traditional beverages and promote the sustainable cultivation of this plant species. Graphical abstract: Image 1